Analisis Pengujian Co-Firing Biomassa Cangkang Kelapa Sawit Pada PLTU Circulating Fluidized Bed (CFB) Sebagai Upaya Bauran Energi Terbarukan - Indra Ardhanayudha Aditya; Fajar Nurrohman Haryadi; Indri Haryani (ROTASI, 2022)
The co-firing characteristics of palm kernel shell biomass are implemented at a Circulating Fluidized Bed (CFB) power plant to determine the effect of co-firing on the potential for corrosion, slagging, fouling, and specific fuel consumption (SFC). Biomass co-firing fuel is mixed in a stockpile with the composition of the co-firing scenario, namely 5%, 10%, 15%, and 20% palm shells for the burn test. Data is retrieved after a stabilization period and then automatically recorded by the data acquisition system. The test results show a lower calorific value, higher volatile matter content, and higher ash content than the coal used during the test. The percentage of oil palm shells in co-firing increases the SFC at the PLTU up to 3,7%. Lower sulfur and HGI content than coal make it more challenging to work. The ratio of base to acid when co-firing 5%, 10%, and 15% palm shells are in the high/weight category. The slagging index when coal burning and co-combustion is still at a safe limit. The Fouling Index for coal combustion and co-firing of 5%, 15%, and 20% of palm shells is in the high category, while co-firing of 10% of palm shells is severe. Based on the sulfur and chlorine data in the fuel, the ratio of 2S/Cl during coal combustion and co-firing is feasible >8. The corrosion potential due to the presence of chlorine is Cl-induced active synthesis minor.